Organization of the expanded cumulus-extracellular matrix in preovulatory follicles: a role for inter-alpha-trypsin inhibitor - Nagyová, Eva (Endocrine regulations, 2015)
It has been shown that following endogenous gonadotropin surge, oocyte-cumulus complexes (OCC) synthesize hyaluronan (HA) in a process called cumulus expansion. During this process, HA associates with proteins and proteoglycans to form the expanded HA-rich oocyte-cumulus extracellular matrix (ECM), where the heavy chains of the serum derived inter-α-trypsin inhibitor family (IαI) bind covalently to HA. No study has been performed on the occurrence and regulation of this process during oocyte maturation in species other than mouse and pig, although, the heavy chains (of IαI)-HA complex was purified from human amniotic membrane. The present review pointing out that: 1/ formation of expanded HA-rich oocyte-cumulus ECM is dependent on the presence of IαI molecules, 2/ the heavy chains of IαI molecules identified in the serum are covalently linked to HA during cumulus expansion in mouse and pig, 3/ the family of IαI molecules can freely cross the blood-follicle barrier, and the follicular fluid collected at any stage of folliculogenesis can be successfully used instead of serum to form expanded cumulus ECM in pig, and 4/ proteins of the IαI family can affect reproductive process by modulating the expression of a large number of cellular genes during a preovulatory period. Finally, this review provides clear evidence that IαI family members present in the serum or follicular fluid become responsible for cumulus expansion, as without these proteins, expanded cumulus HA-rich ECM is not formed and HA is released into medium.
Keywords: inhibitory trypsinu; Animals; Hyaluronic Acid; ovariální folikul; Cumulus Cells; zvířata; Ovarian Follicle; Mice; prasata; Follicular Phase; Swine; folikulární fáze; kyselina hyaluronová; kumulární buňky; Trypsin Inhibitors; myši